Effect of Binder Types and Composition on the Physical and Structural Properties of Alumina Foam - Shamsul Maarif, Mohamad Rusydi; MAT NOOR, FAZIMAH (Research Progress in Mechanical and Manufacturing Engineering, 2025)
This research investigates the influence of various binder types and their compositions on the physical and structural properties of alumina foam, a material recognized for its high-temperature resistance, low density, and porosity. The study systematically evaluates binders such as polyethylene glycol (PEG), carboxymethyl cellulose (CMC), and bentonite to optimize manufacturing techniques aimed at enhancing alumina foam's performance in applications including filtration, thermal insulation, and catalysis. Key findings reveal that the choice of binder significantly affects parameters like packing density, pore size distribution, and mechanical strength. Specifically, PEG/CMC demonstrated superior performance in reducing shrinkage at higher binder concentrations, while bentonite contributed to increased density but lower porosity. The results underscore the potential for refining fabrication methods and expanding the applications of alumina foams in diverse industries by balancing binder composition to achieve desired material characteristics.